The role of technology management in the development of digital platforms of the banking system ("Journal "U". Economy. Management. Finance.", 2024)
Technology management plays an important role in the development of digital platforms in the banking sector. He is engaged in data analytics, open banking, digitalization of payments and integration of banks with fintech companies. All this helps to improve the service, increase the security of transactions and create new opportunities for the development of banks' infrastructure. This article examines the role of technology management in the development of digital platforms of the banking system.
Keywords: technology management; banking system; digital platforms; security